FAKTOR-FAKTOR YANG MEMPENGARUHI KERAWANAN PANGAN RUMAH TANGGA MISKIN DI DESA WIRU KECAMATAN BRINGIN KABUPATEN SEMARANG - sari, Mardiana Ratna; Prishardoyo, Bambang (JEJAK: Jurnal Ekonomi dan Kebijakan, 2009)
The aims of this study are for knowing the factors that influence the food crisis, for analyzing theinfluences of every variable under study, and for knowing the appropriate strategy to eradicate the foodcrisis. The population of this study is 612 families which suffer from the food crisis. Then, the sample is86 families. It is collected by using Cluster Proportional Random Sampling Technique. The variables inthis study are income, education, productive asset ownership and food crisis. The methods used incollecting the data are documentation and questioner. The methods for analyzing the data are multipleregression and SWOT analysis. Income, education and productive asset ownership simultaneously andstrongly influence the families that suffer from food crisis in Wiru village. It can be seen from the result ofF test which is 31 and its significance which is 0,00. Next, the coefficient of partial regression of incomeand food crisis is-0253, the coefficient of education is -0,531, the coefficient of productive assetownership is -0,398 and its determination coefficient is 52%. The appropriate strategy used foreradicating food crisis should be a strategy of horizontal and stability integration. It focuses on theprogram that wants to be achieved and the program based on the familiesÃ¢â¬â¢ economic growth and power.The conclusions of this study are: (1) there is a negative influence between X and Y variables. It meansthat the higher the income, education and productive asset ownership of a family, the family will havesmaller risk in suffering from food crisis (2) the strategy used for eradicating the food crisis is horizontalintegration.Keywords: Income, education, and productive asset ownership.